Productivity trade-off with different water regimes and genotypes of rice under non-puddled conditions in Eastern India - Kar, Ipsita; Sudhir-Yadav; Mishra, Amit; Behera, Basudev; Khanda, Chandramani; Kumar, Virender; Kumar, Ashok (Elsevier, 2018)
"Increasing farm labor scarcity and depletion of natural resources such as water are posing a major threat to the sustainability of traditional puddled transplanted rice (PTR) farming in Eastern India. Dry-seeded rice (DSR) or non-puddled transplanted rice (NPTR) could be used as an alternative to PTR. To understand the trade-off with different water management and rice genotypes under non-puddled conditions, a field experiment was conducted during 2014–2015 on a sandy clay loam soil of Bhubaneswar, Odisha. The treatments for water regimes were based on soil water tension (no stress, 10 kPa, and 40 kPa) at 15-cm soil depth and the cultivars used in the study were inbreds (Lalat and Sahbhagi Dhan) and hybrids (Arize® 6129, 6444, and US 323). In both years, rice yields were higher in the dry season than in the wet season. However, both establishment methods performed similarly in all the seasons. With an increase in water stress, there was a significant decline in yield and yield attributes in the dry season. Irrigation input in the dry season was roughly more than double that in the wet season. Irrigation input was relatively higher in DSR than in NPTR in all the seasons, which might be because of an extra irrigation required for DSR crop establishment than for transplanting in non-puddled conditions where watering is done only for ease of transplanting. There was irrigation saving of 25% and 58% in 10 kPa and 40 kPa, respectively, compared to no stress in the dry season. A consistent trend of an increase in irrigation water productivity (WPI) and input water productivity (WPI+R) was observed with an increase in stress. Arize® 6444 produced the highest grain yield, irrigation and input water productivity, and its performance was also better in terms of tiller density, LAI, and biomass. Our findings highlight the potential of hybrids compared with inbreds and their performance under DSR was found to be superior. Even though the yield in no stress was slightly higher than in 10and kPa, the irrigation water savings in 10 kPa were distinctly significant."